Proposal of Methodology Based on Technical Characterization and Quantitative Contrast of CO2 Emissions for the Migration to Electric Mobility of the Vehicle Fleet: Case Study of Electric Companies in Ecuador - Paola Quintana; Rodrigo Ullauri; Omar Ramos; David Gaona; Javier Martínez-Gómez (World Electric Vehicle Journal, 2025)
This study aims to evaluate the feasibility of replacing internal combustion vehicles (ICVs) with homologated electric vehicles (EVs) within Ecuador’s electricity supply companies, using a structured methodology to ensure operational efficacy and emissions reduction. This was carried out by considering a methodology that allows standardized decision criteria for replacement through determining specific requirements, contrasting technical characteristics, and estimating emissions reduction without compromising the development of transportation daily activities within the companies. The results showed that there are three main categories of combustion-powered vehicles that have electric counterparts, for they are suitable to be replaced under certain operation parameters with a significant reduction in the annual CO2 emissions of around 85%. However, considering market availability and technical constraints, a realistic migration scenario suggests 56% reduction in CO2 emissions. Electric mobility presents a compelling opportunity for decarbonization; achieving true sustainability will require the continued diversification and decarbonization of the national electricity supply, given that 90% of electricity production is based on renewable energy.